E-Library at Aceh Provincial Language Center - Sahruddin, Sahruddin; Salam, Abdus (Lembaga KITA, 2021)
The book data information system at the Aceh Provincial Language Center still uses conventional methods in book data collection. The large number of printed manuscripts that were entered and the transaction process caused many difficulties in controlling bookkeeping. In addition, data processing also takes a long time. From the background description, the authors define the problem only in how the E-library Database Management System at the Aceh Provincial Language Headquarters and the design of the E-library Database Management System at the Aceh Province Language Center Office are web-based. The purpose of the discussion is to find out the E-library Database Management System at the Aceh Provincial Language Headquarters and to design a web-based E-library Database Management System at the Aceh Province Language Headquarters. For the perfection of this report, the authors collected data using several data collection methods, including using field studies and literature studies. The E-library Database Management System makes it easy for the Aceh Provincial Language Headquarters to evaluate the handling of e-libraries and with this application, it can overcome problems that exist at the Aceh Provincial Language Head Office because it speeds up reporting and reduces human errors.